2018
DOI: 10.15766/mep_2374-8265.10678
|View full text |Cite
|
Sign up to set email alerts
|

A Simulated Case of Acute Salicylate Toxicity From an Intentional Overdose

Abstract: Introduction: Salicylate poisoning is a serious toxicologic problem with a complex pathophysiology that requires prompt diagnosis and action for a favorable outcome. A simulated experience in the evaluation and management of an aspirin-overdose patient allows learners to construct a differential diagnosis from an array of symptoms and signs, analyze a mixed acid-base disturbance, and explore the multistep management of this disorder. Methods: This simulation exercise was designed for second-year medical studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Students completed a 5-point Likert-type scale survey in both studies, which demonstrated high acceptability and engagement with the case simulations. 29,30 Since student satisfaction and exam performance are significantly and positively correlated with one another, 3134 it is valid to consider student preference when choosing teaching methods. Several papers conducted quantitative studies to assess the impact of HFS on the application of theoretical knowledge in pharmacy students using the pre-simulation and post-simulation test intervention method.…”
Section: Resultsmentioning
confidence: 99%
“…Students completed a 5-point Likert-type scale survey in both studies, which demonstrated high acceptability and engagement with the case simulations. 29,30 Since student satisfaction and exam performance are significantly and positively correlated with one another, 3134 it is valid to consider student preference when choosing teaching methods. Several papers conducted quantitative studies to assess the impact of HFS on the application of theoretical knowledge in pharmacy students using the pre-simulation and post-simulation test intervention method.…”
Section: Resultsmentioning
confidence: 99%
“…Upon entering a room in a simulated ED, teams had 15 minutes to complete a focused history and physical exam of the patient, interpret arterial blood gas and basic metabolic panel data, and administer treatment based on key findings and a presumptive diagnosis. This simulation exercise was successful in exposing students to the clinical presentation of salicylate toxicity and giving them the opportunity to apply and synthesize basic science knowledge during the scenario (22).…”
Section: Discussionmentioning
confidence: 99%
“…Other learning resources related to metabolic acidosis exist; however, most of these resources are geared solely toward the identification and management of toxin ingestions. [1][2][3][4][5] Although these are clinically important medical emergencies, metabolic acidosis due to toxin ingestion remains a relatively rare clinical encounter. Metabolic acidoses due to renal failure, bicarbonate losses, or lactic acidosis are much more common conditions, and the appropriate medical management of each is relevant to any inpatient medical provider.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the newer, more engaging resources are simulations of acute toxin ingestions, which require a high-fidelity patient simulator, medical equipment, and multiple faculty members. [1][2][3][4][5] Many of these simulation-based resources are focused on higher-level cognitive and procedural competencies surrounding the acute management of a patient in the emergency department. These simulations mostly target emergency department and pediatrics residents, as they are training to be team leaders in the acute care setting.…”
Section: Introductionmentioning
confidence: 99%